Efficacy of Knee Taping in addition to a Supervised Exercise Protocol to Manage Pain and Functional Status in Individuals with Patellofemoral Osteoarthritis: A Randomized, Controlled Clinical Trial - Mudasir Nazar Shah; Mohammad Abu Shaphe; Mohammed Qasheesh; Mohammad Kashif Reza; Ahmad H. Alghadir; Amir Iqbal; Priyadarshani Bhat (Pain Research and Management)
Purpose. This study aimed to investigate the effect of knee taping in addition to a supervised exercise protocol on the pain intensity and functional status of individuals with patellofemoral osteoarthritis (PF OA). Methods. The study was based on a randomized, controlled pretest-posttest experimental group design. Following an initial screening, forty people with PF OA (mean age 55, range 40–60) were randomly assigned to one of two groups, Group A or Group B (n = 20 each). Group A underwent knee taping and participated in a supervised exercise program, whereas Group B only participated in a supervised exercise program. For four weeks, both groups received their prescribed treatment five consecutive days each week. At baseline (day 1 preintervention) and 4 weeks postintervention, the visual analog scale (VAS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were obtained. To compare the effect of stipulated interventions within and between groups, paired and unpaired t tests were performed, with the level of significance set at p<0.05. Results. When comparing the outcome scores at 4 weeks postintervention with baseline scores, the within-group analysis revealed significant mean differences for the outcomes within groups A (VAS: MD = −3.08–0.76; T = 9.70; p<0.05 and WOMAC: MD = −7.05–0.81; T = 11.11; p<0.05) and B (WOMAC: MD = −1.6–0.17; T = 2.35; p<0.05), but a nonsignificant mean difference for the outcomes of VAS within group B (∆MD = 0.08 ± 0.03; T = −0.56; p>0.05). Similarly, when the score of VAS (MD = −2.73–1.29; T = −9.17; p<0.05) and WOMAC (MD = −5.95–1.63; T = −5.86; p<0.05) were compared at 4 weeks postintervention, there was a significant mean difference between groups A and B. Conclusions. In people with patellofemoral osteoarthritis, combining knee taping with a supervised exercise protocol was more effective than the supervised exercise protocol alone in relieving pain and enhancing functional status.